Experimental Investigation on high performance concrete using metakaolin - Nikhitha, Chandur; Babu, P. Suresh Chandra; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
This study investigates the flexural behavior of High-Performance Concrete (HPC) beams incorporating Metakaolin (MK) and Rice Husk Ash (RHA) as mineral admixtures. Ten different HPC beam mixes were tested to evaluate their load-bearing capacity, deflection, and cracking behavior. The results show significant improvements in the ultimate load-bearing capacity and deflection performance of the HPC beams compared to the control beam without MK and RHA. The study highlights that the addition of MK and RHA enhances the bond between aggregate and cement paste, leading to a denser concrete matrix, finer pore structure, and greater overall strength. The findings demonstrate that the optimal mix, with 12.5% RHA and 7.5% MK, achieved a 16.67% higher ultimate load than the control, proving the effectiveness of MK and RHA in enhancing the flexural properties of concrete.